Estrategia de educación ambiental para el fortalecimiento de capacidades locales en la Unidad Educativa Rosa Herlinda Zambrano Ganchozo, Piedra de Plata - Bravo Basurto, Juan Carlos (2025)
This research aimed to evaluate an environmental education strategy to strengthen local capacities, targeting students of Rosa Herlinda Zambrano Ganchozo Educational Unit in the rural community of Piedra de Plata, Bolívar, Manabí. Bibliographic, descriptive, and inductive-deductive research methods were applied, along with observation, interview, survey, and training workshop techniques. The study began with the identification of students’ local capacities, followed by the implementation of an environmental education strategy selected by the students. Subsequently, the impact of this strategy on strengthening those capacities was analyzed. The results indicated that, among the 50 surveyed students, 76% of men and 57% of women did not have a clear understanding of environmental topics, particularly regarding the concept of environmental education. The selected strategy involved creating a school garden, which, with a significance level of 0.0001 for both men and women, showed a highly positive impact on strengthening local capacities. After implementing the strategy, students’ knowledge levels increased, demonstrating that they acquired the necessary knowledge to enhance their environmental capacities.